Papilledema as a Marker for Predicting Outcomes in Patients with Moderate Head Injury - Meena, Hariom; Shekhwat, Jitendra; Beniwal, Hemant; Meena, Anita; Choudhary, Suresh Kumar; Singh, Rahul (Indian Journal of Neurotrauma, 2025)
Introduction Papilledema indicates raised intracranial pressure, which is a significant finding in head injury patients. Being a bedside marker, papilledema can be used for predicting the prognosis in head trauma patients.Objective The aim of the study was to assess papilledema as a single prognostic marker in moderate head injury adult patients.Materials and Methods An observational study was done at the Sawai Man Singh Medical College on 120 patients with moderate head injury (Glasgow Coma Scale [GCS] score of 9–12). CT scan and fundoscopy were done in all patients within the first 24 hours and then the patients were followed up for 3 days. Outcomes were noted in terms of Glasgow Outcome Scale (GOS) during a follow-up of 72 hours after admission where a GOS score of 5 was defined as good outcome.Results Papilledema was present in 25 (20.83%) patients, with early papilledema (<24 hours) in 1 (4.00%) patient and delayed papilledema (up to 72 hours) in 24 (96.00%) patients. Common CT findings were contusions (61.67%), subarachnoid hemorrhage (30.83%), and diffuse axonal injury (2.5%). The GCS score was 9 in 45 (37.50%) patients, 10 in 31 (25.83%) patients, 11 in 30 (25.00%) patients, and 12 in 14 (11.67%) patients at admission. Compared with those without papilledema, patients with papilledema had significantly more contusions (84 vs. 55.79%, p = 0.031). There was a significant association of GCS at 24 hours with papilledema (p < 0.05). Even GOS score showed a significant association with papilledema (p < 0.0001). The absence of papilledema demonstrated sensitivity of 96.87% (95% confidence interval [CI]: 89.16–99.62%) and specificity of 41.07% (95% CI: 28.10–55.02%) with an area under the curve of 0.69 (95% CI: 0.60–0.77) for predicting good outcomes.Conclusion Papilledema was present in 25 (20.83%) cases of moderate head injury. The absence of papilledema showed 70.83% predictability for good outcomes, showing a significant association with prognostication of patients allowing its usage for monitoring and management of the patients.
Keywords: Glasgow; head injury; outcomes; papilledema